PERTANGGUNGJAWABAN PIDANA TERHADAP DIREKSI YANG TELAH MELAKSANAKAN PRINSIP KEHATI-HATIAN DALAM BUMN PERSERO (STUDI PUTUSAN MAHKAMAH AGUNG NO.417K/PIDSUS/2014) - Dezky Muji Setyo; Madiasa Ablisar; Mahmul Siregar; Sunarmi Sunarmi (Universitas Sumatera Utara, 2019)
ABSTRACT Based on the result of the research, it can be seen that there is no firm regulation in the Law of Limited Liability Company and State-Owned Law concerning the standard of prudence and good faith standard for the directors in the management of BUMN. The law only describes the duties and obligations of the Board of Directors which will incur legal liability not only from the aspect of civil law but also from the side of the criminal law if it is proven that the Board of Directors performs any acts deviating from its legal obligation in managing the Company that harms the Company. However, the board of directors may also defend against itself through the principle of business judgment rule if it can prove that in carrying out its duties and obligations do not deviate from the law and articles of association of the company and implemented based on the principle of prudence in good faith and honest so that the loss on the Company Not caused by mistakes or omissions caused by the directors themselves. Keywords: criminal responsibility, board of directors, prudential principles, state-owned enterprises